QFN Enterprise / Muhammad Fairuz Naim Fadilah and Nurul Aqilah Abdul Razak - Fadilah, Muhammad Fairuz Naim; Abdul Razak, Nurul Aqilah (2022)
QFN Enterprise was established on 1st May 2022 using Facebook as a social media platform. The business is based on partnership and owned by Muhammad Fairuz Naim Bin Fadilah and Nurul Aqilah Binti Abdul Razak. The name of QFN is combination of the founders’ initials name, which is ‘Qila’ and ‘Fairuz’. This business is controlled and managed by both owners in term of marketing, advertising, and promoting. The motto is “Hanya yang terindah kami sajikan” which shows that the owners want to deliver great food and drink products with affordable price, so that the customer will feel happy and satisfied with the business. QFN Enterprise offer two types of common products which are Chococrispy and Nilofa milk. The main objective for the business is to distribute and drop-ship these famous brands to the customers as an agent and drop shipper. The targeted customers are chocolate and milk lover as well as those people who acknowledge and enjoy these famous brands. The business is well-known among students, family and children. QFN Enterprise offered both courier service and delivery service with charge for those who near to the area. Since the first opening, QFN Enterprise received a lot of good feedback from the customers. QFN Enterprise marketing strategy is to attract loyal customer of Chococrispy and Nilofa milk, as the high demand from loyal customer all around Malaysia help the business to grow. Promotion strategy is also used to increase people awareness of the products and build loyalty to the brands. Therefore, both products by two common brands is a good marketable product of choice that can be further expanded QFN business area.